Ethnic Populism and Bad Taste: Exploring the Kitschification of Slovak Folklore - Jana Migašová (ESPES)
This study is a_compilation of notes on the concept of folkloric kitsch, understood as a_secondary aesthetic product of modernism that specifically participates in shared feelings of national pride in Central European countries. The aesthetic core of folkloric kitsch production involves the decontextualised and redundant use of elements borrowed from original folk art, aiming to communicate originality, authenticity, and national self-sufficiency. In Slovakia, the kitsch mode of presenting folklore is often used not only in the tourism sector but also to promote ideas charged with nationalism, particularly as part of populist political communication. Against the backdrop of reconstructing European and Slovak thought and writing on the relationship between kitsch and politics, this article attempts to reconstruct and explain folkloric kitsch in the realm of painting as a_specific aesthetic vehicle for the powerful ethnic populism.